Constraints on variation, reduplication of semantics, and degrees of freedom: some notes on the computational account of code mixing. Issue 5 (3rd February 2016) - HARTSUIKER, ROBERT J.
Abstract : Goldrick, Putnam and Schwarz (2016 ) propose a very explicit account of code mixing, which nicely draws implications from the well-established findings of coactivation during bilingual language production, and that code mixing is constrained by grammatical principles. This precise characterization will undoubtedly serve as a useful basis for further research on code mixing, second language sentence production, and syntactic learning. However, there are three issues with the account that require further elaboration.